Desarrollo del método de identificación de fluido seminal mediante la técnica de antígeno pros táctico específico para la aplicación en el laboratorio de química forense. - Navarrete Zambrano, Maritza E. (2012)
6 supports most commonly used in a sexual act, with the following cotton, matters, savannah, chair leather upholstery, tile and earth with seminal fluid stains, giving treatment to the samples, to extract the seminal substrate method was applied for maceration.